MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PELAJARAN IPS MENGGUNAKAN STRATEGI LAGU ANAK-ANAK - ILLAH NAFILAH (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2021)
This research is motivated by the low learning outcomes of students in social studies class VIc. The purpose of this study was to describe the application of the children's song strategy in increasing the learning motivation of grade VIc elementary school students at the 005 Titian Resak State Elementary School in 2019, so that by increasing student learning motivation, it will be able to improve student learning outcomes. The data collection technique in this study was a student evaluation test consisting of 6 multiple choice questions and 4 short entry questions to determine student learning outcomes and supported by interviews and observations. Based on the results obtained from this study, it can be concluded that the learning outcomes of Theme 4 (Globalization) Sub-Theme 3 (Globalization and Love of the Homeland) students of class VI C SD Negeri 005 Titian Resak, can improve by using children's song strategies. The increase in learning outcomes can be seen from the initial conditions, the average value is 64.66 with a percentage of the number of students who complete 40%. In the first cycle there was an increase in the average score of 76 with the percentage of students who completed 64%, with a target of 75. Then in the second cycle there was an increase in the average value of 88, with the percentage of students who completed was 88% with a target of 80. ABSTRAKPenelitian ini di latar belakangi oleh rendahnya hasil belajar siswa pada pelajaran IPS kelas VIc. Tujuan penelitian ini adalah untuk mendeskripsikan penerapan strategi lagu anak-anak dalam meningkatkan motivasi belajar siswa kelas VIc Sekolah Dasar Negeri 005 Titian Resak tahun 2019, sehingga dengan meningkatnya motivasi belajar siswa, akan dapat meningkatkan hasil belajar siswa. Teknik pengumpulan data dalam penelitian ini adalah tes soal evaluasi siswa yang terdiri dari 6 soal pilihan ganda dan 4 soal isian singkat untuk mengetahui hasil beajar siswa serta di dukung dengan wawancara dan observasi. Berdasarkan hasil yang di peroleh dari penelitian ini maka dapat disimpukan bahwa hasil belajar Tema 4 (Globalisasi) Sub Tema 3 (Globalisasi dan Cinta Tanah Air) siswa kelas VI C SD Negeri 005 Titian Resak, dapat meningkatkan dengan menggunakan strategi lagu anak- anak. Peningkatan hasil belajar dapat dilihat dari kondisi awal nilai rata-rata sebesar 64,66 dengan persenatse jumlah siswa yang tuntas 40%. Pada siklus I terjadi peningkatan nilai rata-rata sebesar 76 dengan persentase jumlah siswa ynag tuntas 64%, dengan target sebesar 75. Kemudian pada siklus II terjadi peningkatan nilai rata-rata sebesar 88, dengan jumlah persentase siswa yang tuntas adalah 88% dengan target sebesar 80.